Aqueous extracts of Dodonaea viscosa induce potent and selective cytotoxicity in DLBCL cells - Yekelo, Babalwa (Department of Pathology, 2025)
Cancer is a major cause of death globally, with approximately 10 million deaths in 2020. In South Africa, the number of new cancer cases is expected to double by 2030. Non-Hodgkin lymphoma (NHL), which represents a group of cancers originating from lymphoid tissues, was ranked the 11th most common cancer globally, accounting for 544,000 new cases and 260,000 deaths in 2020. In South Africa, NHL ranks among the top five invasive cancers among both males and females. Diffuse large B cell lymphoma (DLBCL), an aggressive B-cell derived cancer is the most prevalent cancer within the NHL group of cancers. DLBCL can be grouped into two main subtypes, namely the germinal-centre B cell (GCB) and the activated-B cell (ABC) subtypes, with the ABC subtype reported to have a more aggressive clinical course than the GCB subtype. Additionally, DLBCL is an HIV-associated cancer and is, thus, highly overrepresented among HIV-infected individuals. Currently, 30-40 % of DLBCL patients relapse or develop refractory disease following treatment with the standard DLBCL therapy. This figure is worse among HIV-infected DLBCL patients. There is therefore a need to develop more effective therapeutic regimens to treat this cancer. In recent years there has been increasing focus, by cancer sufferers, on the use of alternative therapies for treating their disease. An estimated 80% of the South African population seek health care from traditional healers. Medicinal plants form a major part of the repertoire of tools that these traditional healers use to treat their patients. Many plant species have already been the source of bioactive compounds used to develop currently approved cancer drugs. In the current research, the anti-cancer potential of aqueous extracts of Dodonaea viscosa (DVE), a plant commonly used by traditional healers in the Western Cape region of South Africa, against DLBCL cells, is being investigated. Previously published reports showed that extracts of Dodonaea viscosa can inhibit the growth of several types of cancer cells, including breast, prostate, and colon cancer. There are currently no published reports on the effects of DVE on DLBCL cells. Xv The IC50 of DVE against two DLBCL cell lines (HBL-1 and SU-DHL-4) was determined, relative to a non-cancerous lymphoblastoid cell line (LCL) (PB-LCL-B95-8H) using viability assays. Thereafter, the effect of DVE on proliferation was investigated using proliferation-tracking and colony formation in a semi-solid medium. The effect of DVE on the cell cycle was also investigated. Lastly, induction of apoptosis was determined using microscopy, Annexin V incorporation assay, caspase activity assay, and western blotting to assess the expression of apoptotic markers. Viability assays showed that DVE could potently and selectively inhibit the proliferation of two DLBCL cell lines, namely the GCB cell line SU-DHL-4, and the ABC cell line HBL-1, relative to the non-cancerous lymphoblastoid cell line PB-B95-8H. This converted into a favorable selectivity index of 2.25 for SU-DHL-4 and 3 for HBL-1, demonstrating that DVE preferentially triggers cell death in the cancer cells. The cell-Trace proliferation assay, which tracks live cell proliferation over time, showed a 2.3-fold and 1.3-fold reduction of daughter cells (P2 generation) in the DVE- treated SU-DHL-4 and HBL-1 cells relative to untreated SU-DHL-4 and HBL-1 cells respectively, with the non-cancerous cells being much less affected. The effect of proliferation was further confirmed through a colony-forming assay, which showed potent inhibition of colony formation over 7 days, by DVE, for both cancer cell lines. No notable changes in the phases of the cell cycle (G1, S, G2/M) were observed in all cell lines when exposed to DVE. However, an increase in the sub-G1 population, which is indicative of cell death, was evident in the DVE-treated DLBCL cells. The induction of apoptosis was investigated firstly through microscopy, to assess for the presence of cellular morphological features typical of this mode of cell death. Membrane blebbing, nuclear fragmentation, the presence of apoptotic bodies, and cell shrinkage were observed for both DLBCL cell lines while slight cell swelling was observed for the PB-B95-8H cells. Using the Annexin V incorporation assay, a majority of late apoptotic (64%) and non-viable/necrotic (15%) cells were detected in DVE-treated SU-DHL-4 cells, while mostly early apoptotic cells (49%) were observed for HBL-1. The non-cancerous cell lines were left mostly unaffected. These findings were further supported by the caspase-3/7 activity assay and western blot analysis, which demonstrated that DVE treatment induces the expression of the apoptotic markers PARP-1 and caspase-3 in DLBCL cells, with the SU-DHL-4 cells displaying traces of necrosis, as evidenced by smaller cleaved PARP-1 fragments (74 kDa and below). Xvi Overall, the study shows that aqueous extract of D. viscosa is selectively cytotoxicity towards DLBCL cells, and significantly less toxic towards a corresponding non-cancerous B cell line. Additionally, at the same concentration as DVE, and under the same treatment conditions, the GCB DLBCL cell line was more sensitive to DVE than the ABC DLBCL cell line. This is in line with reports on the more aggressive and resistant nature of the ABC subtype. While this research is the first to demonstrate that extracts of the medicinal plant D. viscosa are cytotoxic toward DLBCL cells, more research is needed to further understand the mechanisms of cell death, as well as to demonstrate these findings in an in vivo model. Additionally, biochemical studies should be done to identify the bioactive compounds responsible for the cytotoxic effects observed.